Human Rights as Limits of Public and Private Power: Another Type of Foundation - Asúnsolo Morales, Carlos R. (DIXI, 2015)
Point of view: Participation by multinational companies in human rights violations has historically been considered a problem of business ethics rather than a problem of law. Purpose: Th main objective of this article is to identify some of the diffilties that a traditional human rights conception, as something that only concerns governments, faces in the process of hegemonic globalization. Description: Using a historic-sociological analysis of the concept of human rights, the fist part aims to show its historical confiuration as limits upon governmental power, excluding private powers from that conception. In a second part, in light of the economic globalization process, it aims to contrast the traditional human rights conception with the new global dynamic, placing emphasis on the fisures that such a Conception involves. Conclusions: Certain key aspects are addressed as the basis for broadening the vision of human rights, including private powers and multinational companies.